Terminal Patient Autonomy and Bioethical Dilemmas: A Legal-Ethical Analysis of Do Not Resuscitate (DNR) Implementation Based on Law No 17/2023: Yudhi Hertanto, Siti Rukayah, Restu Iriani - Yudhi Hertanto; Siti Rukayah; Restu Iriani (STIKes Persada Husada Indonesia, 2026)
Research Objective: Advances in medical technology have created new challenges in determining the end of life, blurring the lines between preserving life and prolonging suffering. This article aims to comprehensively analyze the philosophical, sociological, and legal aspects of terminally ill patients' rights, Advance Directives, and the implementation of Do Not Resuscitate (DNR) within the current Indonesian health law framework. Methodology: The research method used is normative juridical with a statutory and conceptual approach. Results: The results of the study indicate that although Law Number 17 of 2023 concerning Health recognizes the right to refuse medical treatment (Refusal of Treatment) through Article 276 and provides protection for health facilities in Article 192, there is a discrepancy with Article 461 of the National Criminal Code, which still criminalizes the act of taking life on request. This condition triggers significant moral distress among nurses (reaching 47.8% in critical care units) due to procedural uncertainty and the conflict between the principles of beneficence and autonomy. Conclusion: The study concludes that national standardization of Advance Directives and strengthening the role of nurses in palliative care teams are necessary to ensure a dignified death (good death).